Do the size, value, and momentum factors drive stock returns in emerging markets?. (December 2016) - Cakici, Nusret; Tang, Yi; Yan, An
Abstract: This paper investigates the size, value, and momentum effects in 18 emerging stock markets during the period 1990–2013. We find that size and momentum strategies generally fail to generate superior returns in emerging markets. The value effect exists in all markets except Brazil, and it is robust to different periods and market conditions. Value premiums tend to move positively together across different markets, and such inter-market comovements increase overtime and during the global financial crisis.